2018
DOI: 10.15665/dem.v17i1.1657
|View full text |Cite
|
Sign up to set email alerts
|

Internal Marketing: A Model for Implementation and Development

Abstract: Internal marketing (IM) is increasingly recognized as a tool to institutionalize organizational values, improve employee commitment and enhance customer satisfaction. A theoretical model would contribute to its conceptual development and facilitate its application in the organization, enabling to achieve strategic objectives such as customer orientation, organizational commitment, and organization performance. This paper proposes a theoretical model for implementing and developing IM in organizations. The prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 41 publications
0
8
0
5
Order By: Relevance
“…Internal Marketing definition can be summarized as a philosophy of sustainable management to sell and promote company's values, visions, mission and goals to its internal customers through using the application of marketing techniques and human resource management (HRM) principles in order to improve the internal marketplace in which employees enjoy their job experiences (Vu, 2020;Omogbehin, 2014;Bohnenberger et al, 2019;Abd Munir et al, 2015;Akbari et al, 2017;Yuem and Wee, 2020). Internal marketing should start at the top of a company and be communicated downwards into the entire company (Yuem and wee, 2020).…”
Section: Literature Review 21 Internal Marketing 211 Internal Marketing Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Internal Marketing definition can be summarized as a philosophy of sustainable management to sell and promote company's values, visions, mission and goals to its internal customers through using the application of marketing techniques and human resource management (HRM) principles in order to improve the internal marketplace in which employees enjoy their job experiences (Vu, 2020;Omogbehin, 2014;Bohnenberger et al, 2019;Abd Munir et al, 2015;Akbari et al, 2017;Yuem and Wee, 2020). Internal marketing should start at the top of a company and be communicated downwards into the entire company (Yuem and wee, 2020).…”
Section: Literature Review 21 Internal Marketing 211 Internal Marketing Definitionmentioning
confidence: 99%
“…The marketing departments can play a central role in strengthen employees' personal brand (Devi and Srinivasan, 2017;Zeuch, 2016). So that, Bohnenberger et al (2019) proposed the following IM model as shown in figure (4). 6 | P a g e https://jaauth.journals.ekb.eg/…”
Section: Internal Marketing and Human Resource Management (Hrm)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible to develop an attractive marketing strategy aimed at external consumers, however, the final result will substantially depend on the quality of staff work to implement it. Therefore, internal marketing is defined as a focused activity to overcome staff resistance to organizational changes, by its motivation and integration in order to effectively implement company strategies [7].…”
Section: ________________________________________________________________________________________________________________________________mentioning
confidence: 99%
“…Research following these trends has proven that employees with good levels of well-being are employees who have better performance levels. Happy workers provide superior quality services, adding value, promoting competitiveness and innovation, improving motivation and organisational learning, enhancing employees' commitment to their organisations and improving their attitudes and behaviours [2,3,[6][7][8][9][10][11][12]. In this line of thought, the thesis of the happy-productive worker (HPW) arises based on the belief that a happy worker is more productive.…”
Section: Introductionmentioning
confidence: 99%